Kajian perolehan kompetensi keahlian busana butik siswa SMK: studi kasus prakerin di industri pasangan - Sri Handayani; Sri Wening (Jurnal Pendidikan Vokasi, 2016)
Penelitian ini bertujuan untuk mengetahui perolehan kompetensi siswa di setiap DUDI, khususnya busana butik yang memiliki pola pembimbingan berbeda. Penelitian ini menggunakan jenis penelitian studi kasus pendekatan kualitatif. Teknik penentuan Informan menggunakan snowball sampling yaitu instruktur industri, pembimbing, dan siswa SMK N 1 Pengasih yang sedang prakerin. Pengumpulan data menggunakan wawancara, observasi dan dokumentasi. Teknik analisis data mengacu pada analisis model interaktif Miles & Huberman, meliputi pengumpulan data, data condensation, penyajian data, dan deskripsi serta verifikasi kesimpulan. Hasil penelitian adalah (1) praktik yang dijalani siswa sudah relevan dengan kurikulum yang tercantum di sekolah; (2) perolehan kompetensi pada aspek kognitif siswa memperoleh pengetahuan tentang prosedur pembuatan busana butik, pada aspek afektif terbentuk sikap budaya kerja, dan pada aspek psikomotor mampu menyelesaikan pekerjaan busana butik; (3) cara siswa memperoleh kompetensi dengan melakukan: (a) komunikasi; (b) teknik belajar (c) metode kerja praktis; (d) pekerjaan secara mandiri; (e) tindakan dengan tanggung jawab; (f) etos kerja; (g) pengorganisasian dan implementasi kerja dengan baik; (h) bekerja sesuai kepercayaan instruktur industri; (i) pengembangan diri; dan (j) penerapan kompetensi dari sekolah; (4) pencapaian kompetensi siswa yang prakerin di Goet Poespo dan Puspa Rini berada pada level Pemula (novices) sedangkan di L'Mar butik pada level spesialist. A STUDY ON COMPETENCE EXPERTISE ACHIEVEMENT OF BOUTIQUE CLOTHING FOR VOCATIONAL STUDENTS: A CASE STUDYOF INDUSTRY WORK PRACTICE IN PARTNER INDUSTRYAbstractThis research aimed to determine the competence of the students in each "DUDI", especially in fashion boutiques that had different patterns of coaching. The research used a qualitative case study approach. A snowball sampling technique was used to select informants which consisted of the industrial mentors, the school mentor, and students. who were on industry work practice. The data were collected through interviews, and documentation. The data analysis technique refered to the analysis of Miles & Huberman interactive model, including data collection, data condensation, data display, and drawing and verifying conclusions. The result were (1) the practice done by the students was relevant with the curriculum written in the school; (2) in the competence achievement of cognitive aspect the student got the knowledge of boutique dressmaking procedures, in affective aspect, there was a development of work culture attitudes and in the psychomotor aspects, they were able to finish boutique clothes work; (3) the ways of achieving the competence were through: (a) communication, (b) learning techniques, (c)methods, (d) working independently, (e) acting with responsibility, (f) adhering to work ethics, (g) good organization and implementation, (h) working in line with the trust given by the industry instructor, (i)self-development, (j) applying the school competencies; (4) the competence achievement of the students who did industry work practice in Goet Poespo and Puspa Rini was at the novice level, while the ones in L'Mar boutique were at the specialist level.